ANALYSIS OF THE INFLUENCE OF LOCATION, PRICE PERCEPTION, PRODUCT QUALITY AND PROMOTION OF THE PURCHASE DECISION (A STUDY ON PT. ADHI PERSADA PROPERTI) - Hadha Derioktajaya; Farida Indriani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the influence of Place, Price Perception, Product Quality, and Promotion on the Purchasing Decision of apartment units in the Grand Dhika City Lifestyle Jatiwarna area, Bekasi City. The research was conducted on buyers who had purchased apartment units in the area, focusing on PT. Adhi Persada Properti as the developer. As of December 2023, there were 413 buyers, and the sample used consisted of 80 respondents. The method employed is a quantitative approach with a random sampling technique. The collected data was then analyzed to determine the relationship between these factors and consumer purchasing decisions. The results of this study indicate that the variables of Place, Price Perception, and Product Quality do not impact Purchasing Decisions, whereas the Promotion variable has a positive impact on Purchasing Decisions. Furthermore, the study reveals that the variables of Place, Price Perception, Product Quality, and Promotion collectively have a positive impact on Purchasing Decisions. The findings are expected to provide insights into the extent to which each factor influences consumer purchasing decisions in the property sector, particularly in the context of urban property development.